THE FORMATION OF SCULPTURE OF UZBEKISTAN IN THE YEARS OF INDEPENDENCE - Botirov Mukhammadjon Abdukodirovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article provides information about the history of the formation of sculpture in Uzbekistan during the years of independence and the types of sculpture.